Unstable Constitutionalism:Law and Politics in South Asia - Clarisa, Inez Devina; Angelin, Margareta Sevilla Rosa (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2019)
The character of South Asian constitutionalism is desribed by unstable constitutionalism. Unstable constitusionalism refers to a phenomenon in which all participants in national politics appear to be sincerely committed to the idea of constitusionalism – if not always a fully liberal constitutionalism, then certainly one that hopes to establish reasonably permanent institusions with the capacity to address issues of daily governance – yet they stuggle to settle on a stable institutional structure embodying a form of constitutionalism appropriate to their nation. The design issues are significant; a unitary national government, symmetrical or asymmetrical federalism, confederation, and more.